High-frequency high-permeability metal soft magnetic powder core and preparation method thereof

The fine spherical ferrosilicon chromium alloy powder was prepared by water and gas combined atomization method, and combined with screening, passivation, granulation, molding and high-temperature heat treatment, the problem of high eddy current loss caused by large powder particle size in the prior art was solved, and the problem of high eddy current loss caused by large powder particles was realized. Metal soft magnetic materials with high frequency, high magnetic permeability and high unit power density are suitable for high frequency power circuits, simplifying processes and improving performance.

CN119230282APending Publication Date: 2024-12-31SHENZHEN TOPSUN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411757701.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the existing high permeability process, the powder particle size is large, resulting in high eddy current loss and severe heat generation. It is not suitable for high frequency fields and cannot meet the demand for ultra-high switching frequency in DC-DC and power supply circuits.

Method used

The fine and spherical iron-silicon chromium alloy powder was prepared by water and gas combined atomization method, and a high frequency and high magnetic permeability metal soft magnetic powder core was prepared through screening, passivation, granulation, molding and high temperature heat treatment. Simplify process flow, reduce costs, and increase density and permeability.

Benefits of technology

Metal soft magnetic materials with high frequency, high magnetic permeability and high unit power density are realized. They are suitable for MHz-level power circuits with ultra-high switching frequency in DC-DC and power supply circuits, filling the market gap, simplifying production processes, reducing internal stress, and improving Performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230282A_ABST
    Figure CN119230282A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metal soft magnetic materials, in particular to a high-frequency high-permeability metal soft magnetic powder core and a preparation method thereof. The preparation method comprises the following steps: S1, screening magnetically soft alloy powder with a preset particle size; s2, preparing passivation powder; s3, preparing granulation powder; s4, a blank is prepared through compression molding; s5, the blank piece is subjected to curing treatment; and S6, the cured part is subjected to high-temperature heat treatment in vacuum, and the high-frequency and high-permeability metal soft magnetic powder core is obtained. The preparation method disclosed by the invention is simple, mild in reaction condition, low in cost and capable of realizing automatic large-scale production. The high-frequency and high-permeability metal soft magnetic powder core prepared by the invention has high frequency, high magnetic induction intensity and high unit power density, particularly, the internal stress of a metal soft magnetic material is released to the greatest extent by adopting high-temperature heat treatment, the coercive force is reduced, the density and the permeability are remarkably improved, and the high-frequency and high-permeability metal soft magnetic powder core is widely applied to DC-DC and power supply circuits with ultrahigh switching frequency and high magnetic conductivity. And a MHz-level power supply circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal soft magnetic materials, and in particular to a high-frequency and high-permeability metal soft magnetic powder core and a preparation method thereof. Background Art

[0002] With the successful popularization of third-generation semiconductors such as silicon nitride and gallium nitride, integrated inductors, as important magnetic components for corresponding supporting devices (energy storage and energy conversion), urgently need to be upgraded and developed towards the goal of being lighter, thinner, and smaller, in line with the market trend for high-frequency inductors.

[0003] The inventors found in the course of practical research that in the existing high magnetic permeability process methods, the original powder particle size is generally larger than 500 mesh. Although this method can improve the magnetic permeability, the eddy current loss formula P = KfB²δ²V, (P is the eddy current loss power, K is a constant, f is the frequency of the electromagnetic field, B is the magnetic induction intensity, δ is the resistivity of the conductor, and V is the volume of the conductor) shows that the operating frequency and the volume of the conductor are positively correlated with the eddy current loss. The larger the operating frequency and the volume of the conductor, the higher the eddy current loss, the more serious the heating problem will be, and the heating problem will directly affect the service life of the device, so large-particle metal powder is not suitable for high-frequency fields. In addition, under the conditions of the same size and operating frequency, the energy storage capacity of the integrated inductor can be expressed by the unit power density formula (½LI 2 ) / V (L is the inductance value, I is the saturation current, and V is the volume of the integrated inductor). It can be seen that the inductance value and the saturation current are positively correlated with the unit power density, and the volume is negatively correlated with the unit power density. Under the same size, a higher power inductor can be obtained, and under the same power, a smaller size inductor can be obtained.

[0004] Therefore, it is urgent to develop a metallic soft magnetic material with high magnetic permeability and power density to meet the needs of ultra-high switching frequency and MHz-level power supply circuits in DC-DC and power supply circuits. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present application provides a high-frequency, high-permeability metal soft magnetic powder core and a preparation method thereof. The preparation method of the present application is simple, the reaction conditions are mild, and the cost is low. At the same time, the existing process flow is simplified, and large-scale production can be automated. The high-frequency, high-permeability metal soft magnetic powder core prepared by the present application has the advantages of high frequency, high magnetic induction intensity, and high unit power density. In particular, the high-temperature heat treatment is used to release the internal stress of the metal soft magnetic material to the greatest extent, reduce the coercive force, and significantly improve the density and permeability. The high-frequency, high-permeability metal soft magnetic powder core is processed into an integrally formed inductor, which has the advantages of small size and excellent performance. It is widely used in DC-DC and power supply circuits with ultra-high switching frequencies and MHz-level power supply circuits.

[0006] In the first aspect, the present application provides a method for preparing a high-frequency and high-permeability metal soft magnetic powder core, using the following technical solution: A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1. Screening soft magnetic alloy powder of a preset particle size and weighing it according to a preset mass; S2, after the organic solvent and the passivating agent are uniformly mixed with a magnetic stirrer, the soft magnetic alloy powder is added thereto, stirred and mixed, dried, and passed through a 500-mesh sieve to obtain a passivation powder; S3, after the organic solvent and the adhesive are uniformly mixed with a magnetic stirrer, the passivation powder is added thereto and stirred and mixed until a semi-wet state is obtained, and after passing through a 40-200 mesh sieve, the mixture is dried to obtain a granulated powder; S4, adding a release agent to the granulated powder, pressing the powder with a hydraulic press, cleaning the edges and corners to obtain a blank; S5. Put the blank into an oven for curing in an air atmosphere to obtain a cured part; S6. Place the solidified part in a vacuum tube furnace, evacuate it with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core.

[0007] By adopting the above technical scheme, step S1: screen the soft magnetic alloy powder of preset particle size and weigh it according to the preset mass. This step is to ensure that the selected soft magnetic alloy powder has a suitable particle size and shape to meet the needs of subsequent processes. At the same time, weighing according to the preset mass can ensure the consistency and repeatability of the product. Step S2: After the organic solvent and the passivator are evenly mixed with a magnetic stirrer, the soft magnetic alloy powder is added thereto, stirred and mixed, dried, and passed through a 500 mesh sieve to obtain a passivated powder. The purpose of this step is to improve the surface properties of the soft magnetic alloy powder by reacting the passivator with the surface of the metal powder to form a passivation layer, thereby improving its oxidation resistance and corrosion resistance. At the same time, a uniform passivated powder can be obtained by drying and sieving operations. Step S3: After the organic solvent and the adhesive are evenly mixed with a magnetic stirrer, the passivation powder is added thereto and stirred and mixed until a semi-wet state is obtained, and after passing through a 40-200 mesh sieve, it is dried to obtain a granulated powder. The purpose of this step is to make the insulating material coating on the surface of the soft magnetic alloy powder more uniform by mixing with the organic solvent and the adhesive, thereby improving the insulating properties of the material. At the same time, a uniform granulated powder can be obtained by stirring to a semi-wet state, sieving and drying. Step S4: Add a release agent to the granulated powder, perform hydraulic press molding, clean up the corner burrs, and obtain a blank. The purpose of this step is to reduce the friction between the mold and the material by adding a release agent, thereby reducing damage during the molding process. At the same time, a blank with a certain shape and size can be obtained by hydraulic press molding. Finally, cleaning the corner burrs can improve the appearance quality of the product. Step S5: In an air atmosphere, the blank is placed in an oven for curing treatment to obtain a cured part. The purpose of this step is to volatilize or decompose the organic matter in the material by heating, thereby enhancing the mechanical strength and stability of the material. At the same time, the curing treatment can also eliminate the stress concentration phenomenon inside the material and improve the reliability of the product. Step S6: Place the cured part in a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core. The purpose of this step is to adjust the organizational structure and performance parameters of the material, such as density, coercive force, etc., through high-temperature heat treatment. At the same time, oxidation reactions can be avoided in a vacuum environment to ensure the quality stability of the product.

[0008] Preferably, in step S1, the soft magnetic alloy powder is an iron-silicon-chromium alloy powder, which comprises, by mass percentage, Si 4.5-6.0wt%, Cr 4.0-6.0wt%, Mn 0.01-0.03wt%, and the remainder is Fe.

[0009] Preferably, the preparation process of the iron-silicon-chromium alloy powder is a water-gas combined atomization method, and the particle D50 of the iron-silicon-chromium alloy powder is 1-12 μm.

[0010] By adopting the above technical scheme, the water-gas combined atomization method can produce Fe-Si-Cr alloy powder with fine particle size and high sphericity, and its particle D50 is 1-12um. This fine and uniform particle size helps to improve the fluidity and compactness of the powder, so as to obtain higher density and more uniform structure in the subsequent molding process. The Fe-Si-Cr alloy powder produced by the water-gas combined atomization method has uniform chemical composition and small segregation. This means that each powder particle has a consistent chemical composition, which is crucial to ensure the performance consistency of the final product. Fine and highly spherical powder particles help to improve the magnetic properties of the powder because such particles are more easily oriented in the magnetic field, thereby improving the magnetic permeability. Powder particles with fine particle size and high sphericity help to improve processing performance, making it easier to achieve high density and high strength during molding and sintering. Fe-Si-Cr alloy powder has good rust resistance, which reduces the need for rust prevention treatment in subsequent processes and simplifies the process flow. The Fe-Si-Cr alloy powder produced by the water-gas combined atomization method has low loss characteristics, which means that in high-frequency applications, the energy loss of the material is small, which helps to improve the efficiency of components such as inductors. This powder has a high saturation magnetic induction intensity, which is very beneficial for improving the performance of components such as inductors. Iron-silicon-chromium alloy powder has good thermal stability and oxidation resistance, and can maintain stable performance in high temperature environments, which is crucial for high-temperature heat treatment steps. The water-gas combined atomization method is a relatively environmentally friendly production method because it reduces pollution to the environment. In the present application, these properties work together to make iron-silicon-chromium alloy powder an ideal choice for preparing high-frequency and high-permeability metal soft magnetic powder cores. By using this powder, soft magnetic materials with excellent magnetic properties, high frequency response and high unit power can be produced. These materials are particularly suitable for ultra-high switching frequencies in DC-DC and power supply circuits, and MHz-level power supply circuits. In addition, these characteristics also help to simplify the production process, reduce costs, and improve product reliability and performance.

[0011] Preferably, in step S2, the passivator is at least one of phosphoric acid, aluminum dihydrogen phosphate, phytic acid and oleic acid; the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol; the amount of the organic solvent is 6-15wt% of the mass of the soft magnetic alloy powder, and the amount of the passivator is 0.1-1.0wt% of the mass of the soft magnetic alloy powder; the speed of the magnetic stirrer is 300r / min, and the stirring temperature is 35°C; the drying temperature is 80-100°C, and the time is 50-120min.

[0012] Preferably, in step S3, the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol; the adhesive is at least one of sodium silicate, potassium silicate, modified silicone resin, polyvinyl butyral, and biphenyl phenol epoxy resin; the amount of the adhesive is 1.0-4.0% of the mass of the passivation powder, the amount of the organic solvent is 8-15% of the mass of the passivation powder, the speed of the magnetic stirrer is 400r / min, and the stirring temperature is 25°C; the drying temperature is 60-100°C, and the time is 30-60min.

[0013] Preferably, in step S4, the release agent is at least one of paraffin powder, hexagonal boron nitride, barium stearate, and zinc stearate; the amount of the release agent is 0.1-0.9wt% of the mass of the granulated powder, and the pressure of the compression molding is 8-19T / cm 2 .

[0014] By adopting the above technical solutions, higher molding pressure helps to increase the density of the blank and reduce the porosity. High-density materials can provide better magnetic properties because fewer air gaps mean that magnetic flux lines can pass through the material more smoothly. Appropriate pressure can promote the bonding between powder particles and improve the mechanical strength and structural integrity of the material. This is crucial for subsequent processing and durability in practical applications. At the same heat treatment temperature, the higher the pressure, the greater the magnetic induction intensity and unit power density. This is because high pressure can refine the grains, thereby reducing coercive force and increasing magnetic permeability. At the same time, high pressure also helps to reduce internal stress and further improve material performance. During the compression molding process, precise pressure control helps to ensure that the size and shape of the blank meet the design requirements, which is crucial for subsequent processing and finished product quality. Synergy with high-temperature heat treatment High-temperature heat treatment can release the internal stress of metallic soft magnetic materials to the greatest extent, while high-pressure molding provides a uniform and dense starting state for heat treatment. The two work together to significantly improve the density and magnetic permeability of the final product. The compression molding pressure is 8-19T / cm 2 The pressure range is suitable for automated large-scale production, which not only ensures production efficiency but also ensures consistency of product quality.

[0015] Preferably, in step S5, the process conditions of the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes, keep the temperature for 120 minutes, and then naturally cool to room temperature.

[0016] Preferably, in step S6, the vacuum degree of the vacuum extraction is -0.1 MPa, and the process conditions of the high-temperature heat treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is increased to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is increased to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is increased to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is increased to 660°C-780°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.

[0017] By adopting the above technical scheme, controlling the heating rate can ensure that the stress inside the material is uniformly released, avoiding thermal stress concentration or material deformation caused by rapid heating. A moderate heating rate helps to achieve uniform heating of the material and effective stress release. The vacuum degree of vacuuming is -0.1MPa: vacuuming before high-temperature heat treatment can remove gases and volatile substances in the material, reduce the occurrence of oxidation reactions, and ensure the purity and performance stability of the material. In addition, the vacuum environment can also improve the effect of heat treatment and make the material's organizational structure more compact. Process conditions for high-temperature heat treatment: The first stage: 40min room temperature rises to 150℃, and heat preservation for 40min. This stage is mainly to preheat the material, so that the material gradually adapts to the high temperature environment, and at the same time begins to initially release the internal stress. The second stage: then rise to 300℃ for 40min and keep warm for 40min. As the temperature rises, the internal stress inside the material is further released, and microstructural changes such as phase change and grain growth begin to occur. The third stage: rise to 450℃ for 40min and keep warm for 40min. At this stage, the phase change and grain growth process of the material continue, and the internal stress is more fully released. The fourth stage: 40min rise to 600℃, keep warm for 40min. At this time, the internal structure of the material has changed significantly, the internal stress has been released to the maximum extent, and the coercive force has been significantly reduced. The fifth stage: the last 40min rise to 660℃-780℃, keep warm for 120min, and cool down to room temperature naturally. This stage is the key to the entire heat treatment process. Through long-term heat preservation and slow natural cooling, the organizational structure of the material reaches a stable state, thereby obtaining excellent magnetic properties and physical properties. The synergistic effect of these process conditions makes the high-frequency and high-permeability metal soft magnetic powder core have excellent performance. In particular, the release of internal stress, the control of phase change and the promotion of grain growth during high-temperature heat treatment jointly improve the density, magnetic permeability and magnetic induction intensity of the material. In addition, the vacuum treatment also ensures the purity and performance stability of the material. Therefore, these process conditions in step S6 are crucial for the preparation of high-performance high-frequency and high-permeability metal soft magnetic powder cores.

[0018] In the second aspect, the present application provides a high-frequency and high-permeability metal soft magnetic powder core, which adopts the following technical solution: As a general technical concept, the present application also provides a high-frequency and high-permeability metal soft magnetic powder core prepared by the above-mentioned method for preparing the high-frequency and high-permeability metal soft magnetic powder core.

[0019] In a third aspect, the present application provides an application of a high-frequency and high-permeability metal soft magnetic powder core, using the following technical solution: As a general technical concept, the present application also provides an integrally formed inductor, which is prepared using the above-mentioned high-frequency and high-permeability metal soft magnetic powder core.

[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. Simplify the process flow: By adopting the water-gas combined atomization method to prepare iron-silicon-chromium alloy powder, the traditional soft magnetic material preparation process is simplified, the production cost is reduced, and the production efficiency is improved. At the same time, the powder prepared by this method has fine particle size and high sphericity, which helps to improve the magnetic properties and processing performance of the powder.

[0021] 2. Improve magnetic properties: The iron-silicon-chromium soft magnetic alloy powder prepared by the water-gas combined atomization method has uniform chemical composition and small segregation, which can meet the needs of high-quality applications. In addition, the powder has good thermal stability and oxidation resistance, and can maintain stable performance under high temperature environment. Therefore, the high-frequency and high-permeability metal soft magnetic material products prepared using this powder have higher magnetic induction intensity and unit power density.

[0022] 3. Reduce internal stress: During the curing process, the internal stress of the metal soft magnetic material is not released. Through further high-temperature heat treatment, the internal stress can be released to the greatest extent, the coercive force can be reduced, and the density and magnetic permeability can be significantly improved. This helps to improve the performance of soft magnetic powder cores and other product applications.

[0023] 4. Fill the market gap: In line with the rapid development trend of semiconductors, high-frequency and high-permeability metal soft magnetic materials are applied to DC-DC and power supply circuits with ultra-high switching frequencies and MHz-level power supply circuits to fill the market gap and have a large room for development.

[0024] 5. Environmental advantages: The iron-silicon-chromium soft magnetic alloy powder produced by the water-gas combined atomization method has the advantages of good rust resistance, low loss characteristics, high saturation magnetic induction intensity, etc., and is suitable for applications such as one-piece molded inductors. In addition, the powder does not need to be treated with rust prevention, which simplifies the process flow and can be automated for large-scale production. In short, the iron-silicon-chromium soft magnetic alloy powder produced by the water-gas combined atomization method has significant advantages in terms of particle size, shape, chemical composition, magnetic properties and environmental protection, and is suitable for a variety of high-performance application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments: Figure 1 The morphology of the iron-silicon-chromium soft magnetic alloy powder prepared by the water vapor atomization method adopted in each embodiment. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] In the following examples, the iron-silicon-chromium alloy powder used is prepared by water-gas combined atomization method (prepared in Preparation Example 1), and includes, by mass percentage: Si 4.9wt%, Cr 5.0wt%, Mn 0.02wt%, and the balance Fe. The powder morphology is as follows Figure 1 shown.

[0028] Preparation Example 1 Iron-silicon-chromium alloy powder According to the percentage by mass, weigh the iron-silicon-chromium alloy ingredients: Si4.9wt%, Cr5.0wt%, Mn0.02wt%, the balance is Fe, the total weight is 10kg, add it to the medium frequency melting furnace for melting, and use silicon-calcium alloy deoxidizer for deoxidation and slag removal. When the molten metal temperature reaches 1680℃, pour the molten metal into the atomizing ladle of the atomizing equipment, and the molten metal flows through the atomizing nozzle through the hole at the bottom of the ladle. The annular seam gas atomizing nozzle has a spray vertex angle of 30°, and nitrogen is selected as the inert atomizing gas. The atomizing gas pressure is controlled to be 0.8MPa and the gas flow rate is 3m 3 / min, the angle between the two V-shaped water atomizing nozzles is 30°, the fan angle of the V-shaped nozzle is 25°, the atomizing water pressure is controlled to be 150MPa, the water flow rate is 100L / min, and 0.5% of organic phosphate corrosion inhibitor and 0.1% of polyvinyl alcohol are added to the atomizing medium water. The liquid metal is broken into a large number of fine droplets by the two media of atomizing gas and atomizing water. Then the droplets are cooled and solidified into powder in the atomizing collection barrel, and then dehydrated and vacuum dried to obtain iron-silicon-chromium alloy powder. Example 1

[0029] A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1. The iron-silicon-chromium alloy powder is obtained by water-gas combined atomization pulverization, and the powder particle size D50 is 8.3 μm. Acetone accounting for 15% of the mass of the iron-silicon-chromium alloy powder and phosphoric acid accounting for 0.2% are taken, and the iron-silicon-chromium alloy powder is slowly added thereto. The magnetic stirring speed is 300 r / min and the stirring temperature is 35° C. The stirring is carried out for 8 minutes, and then the mixture is transferred to an oven for drying at a baking temperature of 80° C. and a baking time of 50 minutes. After passing through a 500-mesh sieve, a passivation powder is obtained; S2, take 15% of the mass of passivation powder acetone and 4% of modified silicone resin binder, mix them with magnetic stirring, then slowly add the passivation powder thereto, stir and mix for 20 minutes at a magnetic stirring speed of 400r / min and a stirring temperature of 25°C, then sieve the coated powder through a 40-180 mesh sieve, take a powder with a particle size between 40-180 mesh, then transfer it to an oven for drying, the baking temperature is 80°C, the baking time is 30min, and the granulated powder is dried; S3. Add 0.5% of the weight of the composite lubricant of zinc stearate and paraffin powder (the weight ratio of zinc stearate to paraffin powder is 1:1) to the granulated powder, take 2.5g and mold it at room temperature with a molding pressure of 9T / cm 2 , clean the burrs on the edges and corners to obtain the blank; S4. Place the blank into an oven for curing treatment in an air atmosphere to obtain a cured part; the process conditions for the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.

[0030] S5. Place the cured part into a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature. Example 2

[0031] The same as Example 1, except that in step S5, the temperature is raised to 720° C. and maintained for 120 min in the last 40 min of the fifth stage. Example 3

[0032] The same as Example 1, except that in step S5, the temperature is raised to 780° C. and maintained for 120 min in the last 40 min of the fifth stage. Example 4

[0033] A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1. The iron-silicon-chromium alloy powder is obtained by water-gas combined atomization pulverization, and the powder particle size D50 is 8.3 μm. Acetone accounting for 15% of the mass of the iron-silicon-chromium alloy powder and phosphoric acid accounting for 0.2% are taken, and the iron-silicon-chromium alloy powder is slowly added thereto. The magnetic stirring speed is 300 r / min and the stirring temperature is 35° C. The stirring is carried out for 8 minutes, and then the mixture is transferred to an oven for drying at a baking temperature of 80° C. and a baking time of 50 minutes. After passing through a 500-mesh sieve, a passivation powder is obtained; S2, take 15% of the mass of passivation powder acetone and 4% of modified silicone resin binder, mix them with magnetic stirring, then slowly add the passivation powder thereto, stir and mix for 20 minutes at a magnetic stirring speed of 400r / min and a stirring temperature of 25°C, then sieve the coated powder through a 40-180 mesh sieve, take a powder with a particle size between 40-180 mesh, then transfer it to an oven for drying, the baking temperature is 80°C, the baking time is 30min, and the granulated powder is dried; S3. Add 0.5% of the weight of the composite lubricant of zinc stearate and paraffin powder (the weight ratio of zinc stearate to paraffin powder is 1:1) to the granulated powder, take 2.5g and mold it at room temperature with a molding pressure of 11T / cm 2 , clean the burrs on the edges and corners to obtain the blank; S4. In an air atmosphere, the blank is placed in an oven for curing treatment to obtain a cured part; the process conditions of the curing treatment are: gradually increasing the temperature in the following stages: the first stage is heated to 60°C at room temperature for 30 minutes, and the second stage is kept warm for 30 minutes; the third stage is heated to 90°C for 30 minutes and kept warm for 30 minutes; the fourth stage is heated to 120°C for 30 minutes and kept warm for 45 minutes; the fifth stage is heated to 180°C for the last 45 minutes and kept warm for 120 minutes, and then naturally cooled to room temperature; S5. Place the cured part into a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature. Example 5

[0034] The same as Example 4, except that in step S5, the temperature is raised to 720° C. and maintained for 120 min in the last 40 min of the fifth stage. Example 6

[0035] The same as Example 4, except that in step S5, the temperature is raised to 780° C. and maintained for 120 min in the last 40 min of the fifth stage. Example 7

[0036] A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1, using water-gas combined atomization to obtain iron-silicon-chromium alloy powder, the powder particle size D50 = 8.3μm, taking 6% of the mass of iron-silicon-chromium alloy powder and 0.1% of phytic acid, magnetic stirring and mixing, and then slowly adding the iron-silicon-chromium alloy powder thereto, stirring and mixing at a magnetic stirring speed of 300r / min and a stirring temperature of 35°C for 8min, then transferring to an oven for drying at a baking temperature of 80°C and a baking time of 120min; after passing through a 500-mesh sieve, a passivation powder is obtained; S2, take 8% of the mass of passivation powder and 1% of polyvinyl butyral, magnetically stir and mix, then slowly add the passivation powder thereto, stir and mix for 20 minutes at a magnetic stirring speed of 400r / min and a stirring temperature of 25°C, then sieve the coated powder through a 40-180 mesh sieve, take a powder with a particle size between 40-180 mesh, then transfer it to an oven for drying, the baking temperature is 60°C, and the baking time is 60min to obtain granulated powder; S3. Add 0.1% of the weight of the composite lubricant of zinc stearate and paraffin powder (the weight ratio of zinc stearate to paraffin powder is 1:1) to the granulated powder, take 2.5g and mold it at room temperature with a molding pressure of 8T / cm 2 , clean the burrs on the edges and corners to obtain the blank; S4. Place the blank into an oven for curing treatment in an air atmosphere to obtain a cured part; the process conditions for the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.

[0037] S5. Place the cured part into a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature. Example 8

[0038] A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1. The iron-silicon-chromium alloy powder is obtained by water-gas combined atomization pulverization, and the powder particle size D50 is 8.3 μm. 12% of butyl acetate and 1% of aluminum dihydrogen phosphate, which account for the mass of the iron-silicon-chromium alloy powder, are taken and mixed by magnetic stirring, and then the iron-silicon-chromium alloy powder is slowly added thereto. The magnetic stirring speed is 300 r / min and the stirring temperature is 35° C. The stirring is carried out for 8 minutes, and then the mixture is transferred to an oven for drying at a baking temperature of 100° C. and a baking time of 50 minutes. After passing through a 500-mesh sieve, a passivation powder is obtained; S2, take 13% of butyl acetate and 3% of biphenyl phenol epoxy resin by mass of passivation powder, mix them with magnetic stirring, then slowly add the passivation powder thereto, stir and mix for 20 minutes at a magnetic stirring speed of 400r / min and a stirring temperature of 25°C, then sieve the coated powder through a 40-180 mesh sieve, take a powder with a particle size between 40-180 mesh, then transfer it to an oven for drying, the baking temperature is 700°C, and the baking time is 40min to obtain granulated powder; S3. Add 0.7% of the weight of the composite lubricant of zinc stearate and paraffin powder (the weight ratio of zinc stearate to paraffin powder is 1:1) to the granulated powder, take 2.5g and mold it at room temperature with a molding pressure of 15T / cm 2 , clean the burrs on the edges and corners to obtain the blank; S4. Place the blank into an oven for curing treatment in an air atmosphere to obtain a cured part; the process conditions for the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.

[0039] S5. Place the cured part into a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.

[0040] Comparative Example 1 A method for preparing a high-frequency and high-permeability metal soft magnetic powder core comprises the following steps: S1. The iron-silicon-chromium alloy powder is obtained by water-gas combined atomization pulverization, and the powder particle size D50 is 19.8 μm. Acetone accounting for 15% of the mass of the iron-silicon-chromium alloy powder and phosphoric acid accounting for 0.2% are taken, and the iron-silicon-chromium alloy powder is slowly added thereto. The magnetic stirring speed is 300 r / min and the stirring temperature is 35° C. The stirring is carried out for 8 minutes, and then the mixture is transferred to an oven for drying at a baking temperature of 80° C. and a baking time of 50 minutes. After passing through a 500-mesh sieve, a passivation powder is obtained; S2, take 15% of the mass of passivation powder acetone and 4% of modified silicone resin binder, mix them with magnetic stirring, then slowly add the passivation powder thereto, stir and mix for 20 minutes at a magnetic stirring speed of 400r / min and a stirring temperature of 25°C, then sieve the coated powder through a 40-180 mesh sieve, take the powder with a particle size between 40-180 mesh, and then transfer it to an oven for drying at a baking temperature of 80°C for 30 minutes to obtain granulated powder; S3. Add 0.5% of the weight of the composite lubricant of zinc stearate and paraffin powder (the weight ratio of zinc stearate to paraffin powder is 1:1) to the granulated powder, take 2.5g and mold it at room temperature with a molding pressure of 9T / cm 2 , clean the burrs on the edges and corners to obtain the blank; S4. Place the blank into an oven for curing treatment in an air atmosphere to obtain a cured part; the process conditions for the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.

[0041] S5. Place the cured part into a vacuum tube furnace, evacuate with a mechanical pump, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.

[0042] Comparative Example 2 The same as comparative example 1, except that in step S5, the temperature is raised to 720° C. and maintained for 120 min in the last 40 min of the fifth stage.

[0043] Comparative Example 3 The same as comparative example 1, except that in step S5, the temperature is raised to 780° C. and maintained for 120 min in the last 40 min of the fifth stage.

[0044] Comparative Example 4 Same as Comparative Example 1, except that in step S3, the molding pressure is 11T / cm 2 .

[0045] Comparative Example 5 The same as comparative example 4, except that in step S5, the temperature is raised to 720° C. and maintained for 120 min in the last 40 min of the fifth stage.

[0046] Comparative Example 6 The process is the same as that of comparative example 4, except that in step S5, the temperature is raised to 780° C. and maintained for 120 min in the last 40 min of the fifth stage.

[0047] Comparative Example 7 The same as Example 1, except that the high temperature heat treatment in step S5 is not performed.

[0048] Comparative Example 8 Same as Comparative Example 7, except that in step S3, the molding pressure is 11T / cm 2 .

[0049] The high-frequency and high-permeability metal soft magnetic powder cores prepared in the above-mentioned embodiments and comparative examples are magnetic rings with an outer diameter of 13 mm and an inner diameter of 8 mm.

[0050] Performance Testing The magnetic rings prepared in Examples 1 to 6 and Comparative Examples 1 to 8 were sampled respectively. The magnetic rings were made of 0.65 mm enameled wire and wound with 14 turns. Inductance tests were performed in accordance with standard SJ20966-2006. The test results are shown in Tables 1 and 2.

[0051] Use CHROMA 19073 resistivity tester to test the insulation resistance at the diameter of the magnetic ring, then wind the coil on the surface of the magnetic ring, use MICROTEST 6377 (LCR meter) to test the inductance of the magnetic ring, and MICROTEST 6220 (DC bias current source) to test the saturation current of the magnetic ring. Then calculate the effective magnetic permeability of the magnetic ring according to the formula μe=(L*Le*10000) / (4*3.1415*Ae*N2), where μe: effective magnetic permeability, L: inductance (μH), Le: effective magnetic path length (mm), Ae: effective cross-sectional area (mm 2 ),N: number of coil turns; The height was measured with a vernier caliper; Unit power density calculation formula = (½LI 2 ) / V (L is the inductance value, I is the saturation current, and V is the volume of the integrated inductor).

[0052] Table 1 Inductance test

[0053] Table 2 Inductance values ​​of magnetic rings at different frequencies between 1-10MHz

[0054] Analyzing the data in Table 1, we can see that: 1) By comparing the parameters of Examples 1 to 6 and Comparative Examples 1 to 6, it can be seen that under the same pressure and the same high-temperature heat treatment temperature, the smaller the initial particle size of the iron-silicon-chromium alloy powder, the lower the height, the greater the density, the greater the magnetic induction intensity and the unit power density.

[0055] 2) Through the comparison of parameters of Example 1-Example 3, Example 4-Example 6, Comparative Example 1-Comparative Example 3, Comparative Example 4-Comparative Example 6, it can be seen that under the same pressure, the higher the heat treatment temperature, the greater the magnetic induction intensity and unit power density.

[0056] 3) It can be seen from the data of Example 1 and Example 4, Example 2 and Example 5, Example 3 and Example 6, Comparative Example 1 and Comparative Example 4, Comparative Example 2 and Comparative Example 5, Comparative Example 3 and Comparative Example 6, Comparative Example 7 and Comparative Example 8 that at the same heat treatment temperature, the higher the pressure, the greater the magnetic induction intensity and unit power density.

[0057] 4) It can be seen from the data of Examples 1 to 3 and Comparative Example 7, Examples 4 to 6 and Comparative Example 8 that under the same pressure, the magnetic flux density and unit power density of the magnetic ring after secondary annealing heat treatment are higher than those of the untreated one.

[0058] Analyzing the data in Table 2, we can see that: Table 2 shows the inductance values ​​of the magnetic rings at different frequencies between 1 and 10 MHz. It can be seen from Table 2 that the overall trend of Examples 1 to 6 and Comparative Examples 7 and 8 is relatively gentle as the frequency increases, while Comparative Examples 1 to 6 show a gradually increasing trend. It can be seen that the iron-silicon-chromium alloy powder with an initial particle size of less than 500 meshes is more stable in a high-frequency environment.

[0059] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a high-frequency and high-permeability metal soft magnetic powder core, characterized in that: The following steps are involved: S1. Screening soft magnetic alloy powder of a preset particle size and weighing it according to a preset mass; S2, after the organic solvent and the passivating agent are uniformly mixed with a stirring device, the soft magnetic alloy powder is added thereto, stirred and mixed, dried, and passed through a 500-mesh sieve to obtain a passivating powder; S3, after the organic solvent and the adhesive are uniformly mixed with a stirring device, the passivation powder is added thereto, stirred and mixed, dried to a semi-wet state, passed through a 40-200 mesh sieve, and dried to obtain a granulated powder; S4, adding a release agent to the granulated powder and stirring evenly, then molding, cleaning the edges and corners, and obtaining a blank; S5. Curing the blank under air atmosphere to obtain a cured part; S6. Place the cured part into a vacuum tube furnace, evacuate the vacuum, and then perform high-temperature heat treatment to obtain a high-frequency and high-permeability metal soft magnetic powder core; wherein the vacuum degree of the evacuation is -0.1MPa, and the process conditions of the high-temperature heat treatment are: gradually increase the temperature in the following stages: in the first stage, the temperature is raised to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is raised to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C-780°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.

2. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 1, characterized in that: In step S1, the soft magnetic alloy powder is an iron-silicon-chromium alloy powder, which comprises, by mass percentage, Si 4.5-6.0wt%, Cr 4.0-6.0wt%, Mn 0.01-0.03wt%, and the balance is Fe.

3. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 2, characterized in that: The iron-silicon-chromium alloy powder is prepared by a water-gas combined atomization method, and the particle D50 of the iron-silicon-chromium alloy powder is 1-12 μm.

4. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 1, characterized in that: In step S2, the passivator is at least one of phosphoric acid, aluminum dihydrogen phosphate, phytic acid and oleic acid; the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol; the amount of the organic solvent is 6-15wt% of the mass of the soft magnetic alloy powder, and the amount of the passivator is 0.1-1.0wt% of the mass of the soft magnetic alloy powder; the rotation speed of the stirring equipment is 300r / min, and the stirring temperature is 35°C; the drying temperature is 80-100°C, and the time is 50-120min.

5. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 1, characterized in that: In step S3, the organic solvent is at least one of ethyl acetate, butyl acetate, acetone and anhydrous ethanol; the adhesive is at least one of sodium silicate, potassium silicate, modified silicone resin, polyvinyl butyral, and biphenyl phenol epoxy resin; the amount of the adhesive is 1.0-4.0% of the mass of the passivation powder, the amount of the organic solvent is 8-15% of the mass of the passivation powder, the speed of the stirring equipment is 400r / min, and the stirring temperature is 25°C; the drying temperature is 60-100°C, and the time is 30-60min.

6. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 1, characterized in that: In step S4, the release agent is at least one of paraffin powder, hexagonal boron nitride, barium stearate, and zinc stearate; the amount of the release agent is 0.1-0.9wt% of the mass of the granulated powder, and the pressure of the compression molding is 8-19T / cm 2 .

7. The method for preparing a high-frequency and high-permeability metal soft magnetic powder core according to claim 1, characterized in that: In step S5, the process conditions of the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.

8. A high-frequency and high-permeability metal soft magnetic powder core, characterized in that: The high-frequency and high-permeability metal soft magnetic powder core is prepared by the preparation method of the high-frequency and high-permeability metal soft magnetic powder core described in any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method of metal soft magnetic powder core resistant to high-temperature heat treatment

    CN107578872A

  • Low-chromium rust-proof iron-silicon-chromium magnetic powder core and preparation method thereof

    CN115798854A

Cited By

  • Iron-silicon-chromium alloy soft magnetic powder core and preparation method thereof

    CN119542020A

  • A kind of iron-silicon-chromium alloy soft magnetic powder core and preparation method thereof

    CN119542020B